The Evaluatıon Of Perıodontal Tıssue Health And Oral Hygıene Durıng The Retentıon Perıod - Müfide Dinçer; Nazlı Tümer; Berna Ünsal (Galenos Yayinevi, 1998)
The purpose of this investigation was to evaluate the effects of two retention appliances, having acrylic and non-acrylic parts, on periodontal tissue health and oral hygiene. The material of this investigation was composed of periodontal tissue health and oral hygiene measurements of 22 cases, having a sagitally class 1 skeletal type and Angle class I and/or class II dental relationship. The upper and lower first premolars were extracted and each case was treated with standart edge-wise therapy. Subjects were divided into two groups, each consisting of 11 individuals. A Sarhan appliance was applied to the cases in the first group, whereas a Hawley appliance was applied to the cases in the first group, whereas a Hawley appliance was applied to the cases in the second group. The measurements of the cases were evaluated at the beginning and at the end of ninth month of the retention period. Statistical evaluation was carried out by Wilcoxon and Mann Whitney U tests. At the end of the study, the decrease in the values of the gingival and plaque in-deq of the Sarhan group was found to be significantly important. Although periodontal tissue health and oral hygiene were preserved for both appliances, the Sarhan appliance was found to be more effective for the preservation of the periodontal tissue healtn and oral hygiene.